La participación ciudadana en la organización para el desarrollo comunitario del barrio Punzara Chico de la ciudad de Loja, y la intervención del Trabajador Social - Quezada Hurtado, Thalia Michelle (2018)
The present investigation called: "CITIZEN PARTICIPATION IN THE ORGANIZATION FOR THE COMMUNITY DEVELOPMENT OF THE PUNZARA CHICO DISTRICT OF THE CITY OF LOJA, AND THE INTERVENTION OF THE SOCIAL WORKER", makes reference to the citizen participation as an initiative of each individual, whose goal is the promotion of community development; In this context, the question of science was raised: How does citizen participation influence the organization for community development in the Punzara Chico neighborhood? The purpose of the research is to promote citizen participation in the organization for the community development of the neighborhood, for it was necessary to base theoretical and scientific categories that support the object of study, elaboration of a current diagnosis of citizen participation to finally be designed a proposal for social intervention. To carry out the research, the Participatory Action Research (IAP) methodology was used in its three main stages; In the first phase, contact with the community itself allowed a rapprochement with stakeholders, second phase, assessment of needs, made it possible to assess the needs of the community and prioritize according to its importance and finally, programming and execution of the action plan where the residents proposed alternative solutions. in front of the problematic detected. With the support of techniques and instruments such as: observation, participatory diagnosis, the interview applied to the managers of the neighborhood - 5 - and the survey applied to 90 residents, which allowed us to interpret and analyze the causes of the problem under study. The main findings obtained in the field research are that currently the neighborhood Punzara Chico does not have a neighborhood policy which shows that citizen participation is not ideal since this type of participation is considered an act of democracy where residents are who choose their representatives. Also, in the community they do not know what their duties, rights and responsibilities are with the community. The biggest problem lies in the lack of management, participation, planning of all activities aimed at achieving the development of the neighborhood, that is, there is no real citizen participation that contributes to the organization and community development. Taking into account these results, a proposal of social intervention was proposed that aims to encourage citizen participation in the residents to improve the organization of the neighborhood and achieve community development.